Self-care of elderly people after the diagnosis of acquired immunodeficiency syndrome - Graciela Machado de Araujo; Marinês Tambara Leite; Leila Mariza Hildebrandt; Cinthia Cristina Oliveski; Margrid Beuter
ABSTRACT Objective: to characterize the seropositive elderly for the Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome (HIV/AIDS) in their socio-demographic aspects; to understand how the elderly take care of themselves from the diagnosis of HIV/AIDS. Method: Qualitative, descriptive, exploratory research conducted at a Voluntary Counseling and Testing Center with 10 elderly people receiving treatment for HIV/AIDS. The data were analyzed according to the content analysis. Results: Data show the elderly people's lack of knowledge about HIV/AIDS transmission, the experience of being elderly and having HIV/AIDS, caring for oneself and life after diagnosis of HIV/AIDS in their daily lives. Final considerations: The diagnosis of HIV/AIDS seropositivity in the elderly generates a blend of feelings and fears that lead to food changes, adherence to treatment and the renunciation of daily and social habits, manifested as ways of self-care.